2018
DOI: 10.3390/fermentation4040097
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage Aeration Fermentation Strategy to Improve Bioethanol Production by Scheffersomyces stipitis

Abstract: Hardwood spent sulfite liquor (HSSL) is a by-product from pulp industry with a high concentration of pentose sugars, besides some hexoses suitable for bioethanol production by Scheffersomyces stipitis. The establishment of optimal aeration process conditions that results in specific microaerophilic conditions required by S. stipitis is the main challenge for ethanol production. The present study aimed to improve the ethanol production from HSSL by S. stipitis through a two-stage aeration fermentation. Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…KLa values in the range of 2.3 to 5.9 h1 were regarded as having the optimum balance between productivity and yield. In terms of DOT, S. stipitis produced more ethanol when the saturation level was less than 1% [ 61 ].…”
Section: Factors Affecting Fermentation Process Of Traditional Foodsmentioning
confidence: 99%
“…KLa values in the range of 2.3 to 5.9 h1 were regarded as having the optimum balance between productivity and yield. In terms of DOT, S. stipitis produced more ethanol when the saturation level was less than 1% [ 61 ].…”
Section: Factors Affecting Fermentation Process Of Traditional Foodsmentioning
confidence: 99%
“…Papini et al (2012) reported that S. stipitis produces ethanol when oxygen becomes limiting, since reduced oxygen tension induces pyruvate decarboxylase and alcohol dehydrogenase activity [51]. The optimum oxygen concentration is the main bottleneck of S. stipitis bioethanol production [45], and a new strategy of bioreactor aeration was just described for bioethanol fermentation [30].…”
Section: Erlenmeyer Flask Co-culture Assaysmentioning
confidence: 99%
“…Bioethanol production from Kraft pulp by several fermentation configurations was studied, namely separate hydrolysis and fermentation (SHF) [22,23], simultaneous saccharification and fermentation (SSF) [15,[24][25][26][27], and consolidated bioprocessing [28].Besides hexose sugars, hydrolysates also have a high content in pentoses, mainly xylose, which can reach 25%, meaning that pentoses fermentation is necessary to attain an economically viable 2G bioethanol production [7,29]. Scheffersomyces stipitis was well as Saccharomyces cerevisiae have already been tested for bioethanol production from different LCB feedstocks, including eucalypt spent sulfite liquor [30][31][32], grape skins [33], sugarcane bagasse [34,35], cardoon, and rockrose [36]. The co-culture of hexose-and pentose-fermenting yeasts is a potential solution for this problem, since most well-known natural microorganisms are not able to efficiently ferment both sugars.…”
mentioning
confidence: 99%
“…Furans, i.e., furfural and HMF, inhibit microbial growth and increase the lag phase, decreasing the volumetric ethanol yield and productivity [49]. Low molecular weight organic acids such as acetic, formic, lactic, and levulinic acids are toxic to microorganisms and can affect their growth [47], since they can be transported through cell membrane acidifying the cytoplasm depending on intracellular pH and dissolved oxygen concentration [4,50]. Phenolic compounds like vanillin, syringaldehyde, trans-cinnamic acid, and hydroxybenzoic acid, were reported to inhibit cellulases [51].…”
Section: Pretreatmentmentioning
confidence: 99%
“…Several isolates adapted to HSSL inhibitors were obtained and the most efficient isolate was used for the fermentation of undetoxified HSSL, resulting in an improved performance when compared to the parental strain [133]. The same isolate provided better results using a two-stage aeration fermentation strategy [50]. Takahashi et al (2015) studied the use of anion exchange resins to remove acetic acid from HSSL.…”
Section: Bioethanol Productionmentioning
confidence: 99%